The Effects of a Single Whole-Body Cryotherapy Exposure on Physiological, Performance, and Perceptual Responses of Professional Academy Soccer Players After Repeated Sprint Exercise. Issue 2 (February 2017) - Russell, Mark; Birch, Jack; Love, Thomas; Cook, Christian J.; Bracken, Richard M.; Taylor, Tom; Swift, Eamon; Cockburn, Emma; Finn, Charlie; Cunningham, Daniel; Wilson, Laura; Kilduff, Liam P.
Abstract: Russell, M, Birch, J, Love, T, Cook, CJ, Bracken, RM, Taylor, T, Swift, E, Cockburn, E, Finn, C, Cunningham, D, Wilson, L, and Kilduff, LP. The effects of a single whole-body cryotherapy exposure on physiological, performance, and perceptual responses of professional academy soccer players after repeated sprint exercise. J Strength Cond Res 31(2): 415–421, 2017—In professional youth soccer players, the physiological, performance, and perceptual effects of a single whole-body cryotherapy (WBC) session performed shortly after repeated sprint exercise were investigated. In a randomized, counterbalanced, and crossover design, 14 habituated English Premier League academy soccer players performed 15 × 30 m sprints (each followed by a 10 m forced deceleration) on 2 occasions. Within 20 minutes of exercise cessation, players entered a WBC chamber (Cryo: 30 seconds at −60° C, 120 seconds at −135° C) or remained seated (Con) indoors in temperate conditions (∼25° C). Blood and saliva samples, peak power output (countermovement jump), and perceptual indices of recovery and soreness were assessed pre-exercise and immediately, 2-hour and 24-hour postexercise. When compared with Con, a greater testosterone response was observed at 2-hour (+32.5 ± 32.3 pg·ml −1, +21%) and 24-hour (+50.4 ± 48.9 pg·ml −1, +28%) postexercise (both P = 0.002) in Cryo (trial × treatment interaction: P = 0.001). No between-trial differences were observed for other salivary (cortisol and testosterone/cortisol ratio), blood (lactate and creatine kinase), performance (peak power output), or perceptual (recovery or soreness) markers (all trial × treatment interactions: P > 0.05); all of which were influenced by exercise (time effects: all P ≤ 0.05). A single session of WBC performed within 20 minutes of repeated sprint exercise elevated testosterone concentrations for 24 hours but did not affect any other performance, physiological, or perceptual measurements taken. Although unclear, WBC may be efficacious for professional soccer players during congested fixture periods.